Instytucjonalizacja form rywalizacji politycznej w wyborach do Parlamentu Europejskiego w województwie podkarpackim w 2014 roku - Szczepański, Dominik (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
The purpose of the article is to present institutional forms of political competition treated as arbitrational issue of the authorities based on the election. The analysis was conducted on the basis of the three forms of political competition; namely conflict, public order and the configuration between the ruling party and the opposition. The direct background to the above-mentioned forms was the election to the European Parliament in the Subcarpathian Voivodeship in 2014. Analysis was also carried out taking into consideration specifics of this Voivodeship, when treated as a specific region on the electoral map of Poland.
The institutionalization of the form of political competition in the 2014 election to the European Parliament in the subcarpathian voivodeship
Keywords: political competition; European Parliament; elections; political parties; Subcarpathian Voivodeship